2011
DOI: 10.1021/es103933e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PCDD/F Emissions from Mobile Source Diesel Engines: Impact of Copper Zeolite SCR Catalysts and Exhaust Aftertreatment Configurations

Abstract: This study investigated the impact of copper zeolite selective catalytic reduction (SCR) catalysts and exhaust aftertreatment configurations on the emissions of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) from mobile source diesel engines. Emissions of PCDD/Fs, reported as the weighted sum of 17 congeners called the toxic equivalency quotient (TEQ), were measured using a modified EPA Method 0023A in the absence and presence of exhaust aftertreatment. Engine-out emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…1. This is similar to other reported results from previous studies (Laroo et al, 2011;Liu et al, 2011;Laroo et al, 2013).…”
Section: Pcdd/f Concentrations Congener Profiles and Emission Factorssupporting
confidence: 93%
See 1 more Smart Citation
“…1. This is similar to other reported results from previous studies (Laroo et al, 2011;Liu et al, 2011;Laroo et al, 2013).…”
Section: Pcdd/f Concentrations Congener Profiles and Emission Factorssupporting
confidence: 93%
“…PCB Concentrations (pg Nm Before SCR After SCR Although the performance of SCR, which depends on its type, surface properties and exhaust residence time (Liu et al, 2011), may be one of the reasons, we speculated that the particulate matters and precursors of POPs emitted from diesel engine play an important role on the formation/ destruction of POPs when exhaust passes through SCR. That is because the heavy diesel engine, a 2008 MY 6.7 L Cummins ISB, used in Laroo et al (2011) is more modern than the engine used in our study, and its PCDD/F emission factor (1.89 pg I-TEQ L -1…”
Section: Pcdd/f Concentrations Congener Profiles and Emission Factorsmentioning
confidence: 99%
“…In general, studies have not replicated the Swiss findings, instead reporting consistent reductions in PCDD/F emissions for various aftertreatment configurations, including for engines operated with copper-zeolite (Cu-zeolite) and iron-zeolite (Fe-zeolite) SCR systems, copper/iron-based fuelborne catalysts, and diesel fuels doped with elevated chlorine levels. 14,29,[48][49][50][51] In particular, for a comprehensive testing strategy that employed two different 2010 engines operated over a range of different exhaust aftertreatment configurations (including Cu-zeolite SCRs operated with and without urea; see Table 1) using chlorine-doped diesel fuels (0.6 and 8.4 ppm), Liu et al 29 demonstrated significant reductions (60-80%) in PCDD/F emissions for all aftertreatment configurations, with no impact of elevated chlorine fuel levels ( Figure 4). In addition, Khalek et al 14 reported 99% reductions in dioxin/furan emissions from the four 2007 ACES engines compared to 1998 technology engines (Table 2).…”
Section: Pahs and Other Organic Speciesmentioning
confidence: 99%
“…1 Since the 2008 publication of this review, results from numerous characterizations of NTDE emissions have been published, including Phase 1 findings from the Advanced Collaborative Emissions Study (ACES), 13,14 a series of findings from a collaborative study of the California Air Resources Board (CARB) and the University of Southern California (USC), [15][16][17][18][19][20][21] and other detailed analyses. [22][23][24][25][26][27][28][29] Importantly, these new studies have substantially improved our understanding of how the DEP in NTDE differs from the DEP in TDE in terms of chemical and physical properties that can affect toxicity. In particular, they address whether secondary emissions, such as nitroPAHs and dioxins/furans, may be associated with exhaust aftertreatment systems.…”
mentioning
confidence: 99%
“…No reference works dealing with on-road samplings in passenger vehicles have been found. Table S3 of the supporting information summarizes some published data concerning the main congeners (without toxicity factors), the congeners that contribute to the total toxicity I-TEQ (taking into account the toxicity factors), and the percentage x 100 of Page 5 of 32 A c c e p t e d M a n u s c r i p t 5 PCDFs/(PCDFs+PCDDs) without and with TEF factors [2,3,6,8,[15][16][17][18][19]21,22,24,26,27,[29][30][31][32][33].…”
mentioning
confidence: 99%